Lipid Pathology of the Corpus Callosum in Schizophrenia and the Potential Role of Abnormal Gene Regulatory Networks with Reduced Microglial Marker Expression. (14th September 2020) - Shimamoto-Mitsuyama, Chie; Nakaya, Akihiro; Esaki, Kayoko; Balan, Shabeesh; Iwayama, Yoshimi; Ohnishi, Tetsuo; Maekawa, Motoko; Toyota, Tomoko; Dean, Brian; Yoshikawa, Takeo
Abstract: Structural changes in the corpus callosum have been reported in schizophrenia; however, the underlying molecular mechanism remains unclear. As the corpus callosum is high in lipid content, we analyzed the lipid contents of the corpora callosa from 15 patients with schizophrenia and 15 age- and sex-matched controls using liquid chromatography coupled to tandem mass spectrometry and identified lipid combinations associated with schizophrenia. Real-time quantitative polymerase chain reaction analyses using extended samples (schizophrenia, n  = 95; control, n  = 91) showed low expression levels of lipid metabolism-related genes and their potential upstream transcription factors in schizophrenia. Subsequent pathway analysis identified a gene regulatory network where nuclear factor of activated T cells 2 ( NFATC2 ) is placed most upstream. We also observed low gene expression levels of microglial markers, inflammatory cytokines, and colony-stimulating factor 1 receptor ( CSF1R ), which is known to regulate the density of microglia, in the corpus callosum in schizophrenia. The interactions between CSF1R and several genes in the presently identified gene network originating from NFATC2 have been reported. Collectively, this study provides evidence regarding lipid abnormalities in the corpora callosa of patients with schizophrenia and proposes the potential role of impaired " NFATC2 -relevant gene network-microglial axis" as its underlying mechanism.